The attributes of organizational excellence - Romanowska, Maria (Zarządzanie strategiczne w dobie cyfrowej gospodarki sieciowej, 2020)
The concept of organizational excellence was synthesized in the study. Classification of attributes of excellence was proposed, taking into account its two dimensions – functioning and result. Five attributes were described: coherence, adaptability, intelligence, organizational and economic effectiveness. The evolution of the concept of excellence and its importance for science and management practice was demonstrated.